The Influence of Leadership, Motivation, Compensation, and Supervision on Work Productivity At PT. Gasing Sulawesi in Makassar City - Handayani, Siti Mira; Harrang, Agussalim; Jam'an, Andi; Rusydi, Muhammad; Muchran, Muchriady (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to determine and analyze the influence of leadership, motivation, compensation, and supervision on work productivity at PT. Gasing Sulawesi in Makassar City. This type of research is quantitative research with a sample of 110 respondents using a questionnaire as a source of data collection. The analysis used is Multiple Linear Regression Analysis using the SPSS V.24 application. The results of the research show that: 1. Leadership has an insignificant positive effect on work productivity 2. Motivation has a positive and significant effect on work productivity. 3 Compensation has a positive and significant effect on work productivity. 4. Supervision has a positive and significant effect on work productivity.